Impact of hepatitis B virus surface protein mutations on the diagnosis of occult hepatitis B virus infection - El Chaar, Mira; Candotti, Daniel; Crowther, R. Anthony; Allain, Jean Pierre (Hepatology (Baltimore, Md.), 2010)
Genotype D occult hepatitis B virus (HBV) infections (OBIs) have a high frequency of amino acid substitutions in the major hydrophilic region of the small surface protein (S protein). This possibly reflects an escape mutation mechanism to evade detection by the host immune system. Mutations may also impact the detection of hepatitis B surface antigen (HBsAg) by commercial assays. To test these hypotheses, 20 recombinant HBV genotype D surface proteins from OBI carriers with or without antibody to hepatitis B surface antigen (anti‐HBs) were expressed in yeast. Recombinant surface protein (rS protein) variants were nonreactive with autologous anti‐HBs but reacted weakly with vaccine‐induced anti‐HBs supporting an immune escape mechanism. rS protein variants tested with a wide range of HBs antibodies, and HBsAg commercial assays showed significantly lower antigenic reactivity in anti‐HBs carriers than in donors with antibody to hepatitis B core antigen (anti‐HBc) only. Eight out of 10 recombinant variants from anti‐HBs carriers reacted weakly or were nonreactive with antibodies to HBs as well as with qualitative and quantitative commercial HBsAg assays, whereas eight out of 10 anti‐HBc–only plasmas were fully reactive. rS proteins with substitutions of wild‐type cysteine at positions 121, 124, and 137 were nonreactive or showed poor reactivity. However, mutation of cysteine 147 did not alter reactivity compared with controls. Restoration of cysteines 124 and 137 by site‐directed mutagenesis improved antigenic reactivity. Conclusion: Escape mutation is a mechanism associated with OBI, which also leads to decreased reactivity in HBsAg detection assays. Performance of commercial assays would be improved by the incorporation of OBI mutants in reagent development. (HEPATOLOGY 2010)